Making Innovation Visible in Agile: A Practical Guide to Capturing and Scaling What Works - Abu Bakar, Shamsulkhomar (Avenew Indonesia, 2025)
Innovation often happens on the frontlines of Agile delivery — in stand-ups, retrospectives, and sprint adaptations. Yet in many transformation-heavy organisations, especially within the telecommunications sector, these innovations remain invisible. Teams adapt, but their breakthroughs are undocumented, unvalidated, and unscalable. This white paper introduces the VINE Framework (Value-based Innovation Evaluation) — a lightweight, embedded approach that enables Agile teams to identify, validate, and scale innovation from the ground up. Developed within a large national telco (